A retrospective study of ophthalmologic presentation, management, and outcomes in pediatric patients admitted with abusive head trauma - Yin, Jiawei; Peng, Jie; Zhang, Xuerui; Yang, Yuan; Gu, Victoria Y.; Zhang, Wenting; Liu, Huanyu; Xiao, Haodong; Xu, Yu; Zhao, Peiquan (Frontiers in Medicine, 2024)
Background: Abusive head trauma (AHT) is a severe form of physical abuse leading to significant morbidity and mortality in children, often presenting with complex brain injuries. Among the varied manifestations, ophthalmologic presentations are critical yet underexplored, which may provide essential clues for early diagnosis and management, improving long-term visual and neurological outcomes.Objective: This study aims to explore the manifestation, management, and outcomes of AHT cases within a single center in China over a five-year period, with a focus on the importance of ophthalmologic evaluation in enhancing the diagnosis, management, and outcome predictions of AHT.Methods: A retrospective case series was conducted at a single institution, involving infants diagnosed with AHT from 2019 to 2023. Data on demographics, medical histories, and clinical management were collected. Ophthalmologic examinations including fundus photography, ocular B-scan ultrasound and fundus fluorescein angiography (FFA), were performed to evaluate retinal vasculature and identify peripheral ischemic retina (PIR). Statistical analyses were performed using SPSS ver. 26.0.Results: Eight AHT patients (16 eyes) were included in the study. Bilateral ocular involvement was observed in all patients, with 81.25% exhibiting retinal hemorrhages (RH). Other manifestations included retinal detachment (31.25%) and optic nerve atrophy (18.75%). Clinical interventions varied, with 68.75% of patients undergoing treatments such as laser photocoagulation and anti-vascular endothelial growth factor (VEGF) injections. Among all eyes, 75% showed resolution of RH. Despite treatment, some patients progressed to severe conditions such as retinal detachment (RD) and iris neovascularization (INV).Conclusion: This study emphasizes the importance of a multidisciplinary approach in the diagnosis and management of AHT, particularly by integrating ophthalmological perspectives into patient care. These findings contribute to the understanding of ophthalmologic presentations in AHT.